PENGARUH PENDEKATAN SAVI TERHADAP PENINGKATAN LITERASI STATISTIS DAN MOTIVASI BELAJAR SISWA KELAS VI SEKOLAH DASAR DALAM MATERI PENGOLAHAN DATA - Dian Wahyuningsih; Rosyida Hanifa Zara; Budi Murtiyasa; Sumadi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to evaluate the impact of the SAVI (Somatic, Auditory, Visual, Intellectual) approach on improving statistical literacy and learning motivation of sixth-grade elementary school students in data processing material. The identified problem is that many students struggle to understand and process statistical data and lack motivation to learn. Conventional teaching methods still used at MI Muhammadiyah Caruban are considered less effective. This research uses a quasi-experimental design with pre-test and post-test on the experimental group applying the SAVI approach and the control group using conventional methods. The results show that the experimental group experienced a significant increase in statistical literacy with an average score increase of 20 points (from 65 to 85) compared to the control group, which only increased by 6 points (from 64 to 70). Learning motivation also significantly increased with an average rise of 20 points (from 70 to 90) in the experimental group, while the control group only increased by 7 points (from 68 to 75). Statistical tests show a significant difference between the two groups, with a significance value of p < 0.05 for statistical literacy and learning motivation. These findings indicate that the SAVI approach is proven effective in enhancing students' understanding of statistical data and motivating them to learn.